Reconstruction of Software Component Architectures and Behaviour Models using Static and Dynamic Analysis - Krogmann, Klaus (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2012)
Model-based performance prediction systematically deals with the evaluation of software performance to avoid for example bottlenecks, estimate execution environment sizing, or identify scalability limitations for new usage scenarios. Such performance predictions require up-to-date software performance models. This book describes a new integrated reverse engineering approach for the reconstruction of parameterised software performance models (software component architecture and behaviour).